THE INFLUENCE OF THE CANVA-ASSISTED PROJECT-BASED LEARNING MODEL ON STUDENTS' CREATIVE THINKING ABILITIES IN CLASS V ELEMENTARY SCHOOL POSTER MATERIALS - Vera Ironita Christiani Sihombing; Sutar Oktaviana Tampubolon (International Journal of Teaching and Learning, 2024)
This research aims to determine the effect of the Canva-assisted Project-Based Learning model on students' creative thinking abilities on class V elementary school poster material. This research is a quantitative research with a Quasi-Experimental Design (quasi-experiment) with a non-equivalent control group design type of research design. In this study, both classes, both experimental and control classes, were given a pretest, then given treatment, then the final step was given a posttest. This research uses normality, homogeneity and t-test tests. The results of the normality and homogeneity tests show that the data obtained are normal and homogeneous. The t-test results during the pretest did not change to sig<0.05, namely 0.378. After being given treatment and posttest, the t-test results experienced a change of sig>0.05, namely 0.000. This shows that there are changes before and after being given treatment using the learning model as well as an increase in the results of each indicator of students' creative thinking abilities.